The formation of higher alcohols in rice wine fermentation using different rice cultivars - Wang, Chunxiao; Yuan, Guoyi; He, Yulin; Tang, Jiadai; Zhou, Hongxiang; Qiu, Shuyi (Frontiers in Microbiology, 2022)
Higher alcohols are closely related to the flavor and safety of rice wine. The formation of n-propanol, isobutanol, isoamyl alcohol, and phenylethanol during rice wine fermentations was for the first time investigated in this study among 10 rice cultivars from two main production regions. Rice wine made from Yashui rice, the long-grain non-glutinous rice from Guizhou, produced the highest yields of higher alcohols (487.45 mg/L), and rice wine made from five glutinous rice cultivars produced the lowest yields of higher alcohols (327.45–344.16 mg/L). An extremely strong correlation was found between the starch in rice and higher alcohols in rice wine. Further analysis first showed that the former fermentation period was key for the nutrient consumption and higher alcohol formation, with more than 55% of glucose being consumed and more than 75% of higher alcohols being synthesized in 48 h. Correlation analysis confirmed the strong correlation between nutrient consumption and higher alcohol formation including valine–isobutanol (coefficient higher than 0.8 in seven rice cultivars and higher than 0.6 in three rice cultivars), glucose–isoamyl alcohol (coefficient higher than 0.8 in five rice cultivars and higher than 0.6 in the other five rice cultivars), and glucose–phenylethanol (coefficient higher than 0.8). The correlation of threonine–n-propanol, leucine–isoamyl alcohol, phenylalanine–phenylethanol, glucose–n-propanol, and glucose–isobutanol varied among the rice wines made from 10 rice cultivars. RT-qPCR analysis on five target genes verified the variation caused by different rice cultivars. this study for the first time reported the special formation pattern of higher alcohols during rice wine fermentation, emphasizing the early contribution of glucose metabolism on the formation of isobutanol. This study highlighted the significance of rice selection for making rice wine with good quality and provided theoretical references for the control of higher alcohols, especially in the former period of rice wine fermentation.